Educational Values in Surah Al-Jumu’ah Verses 1-4 from the Perspective of Ibn Kathir - Maulana Rizqi, Anggi; Ahmad Fauzi, Rifqi (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Tempurrejo Ngawi, 2023)
This study aims to explore the educational values found in Surah Al-Jumu'ah verses 1-4 according to Ibn Kathir's exegesis. In its background, the study presents Ibn Qayyim al-Jauziyah's view on education as a holistic process that shapes individual character, morality, and spirituality. The research method used is the analysis of Ibn Kathir's exegesis text to explore the educational values of belief, worship, and morality in the surah. The research findings indicate that Surah Al-Jumu'ah contains important messages about the importance of reliance on Allah, obedience to His commandments, acknowledgment of His greatness, understanding of His attributes, the mission of the Prophet Muhammad, purity, obedience to Allah, seeking knowledge, goodness, wisdom, and reliance on Allah. As a recommendation, this study suggests further exploration of the implementation of these educational values in the context of modern society and their integration into formal and informal education systems to cultivate morally upright generations that contribute positively to society. Thus, this research makes a significant contribution to the understanding and practice of relevant Islamic education in contemporary life.